A VDU experimental setup for fixation disparity evaluation - Sousa, Raul A. R. C. (2011)
A new experimental setup for any standard Video Display Unit (VDUET) with dichromatic glasses was developed for fixation disparity (FD) accessing. A computer software produce a dark field with white targets for central and peripheral fusion and two lines colors red and green for dissociated vision with the use of red and green filters. These lines can be moved right or left by the subject, until are seen apparently aligned. The real displacement between the lines is then recorded. The fixation curve (FC) is obtained by the interposition of prisms before one or both eyes, as in a regular commercial FD test. A comparison for FD and measurement time between this experimental setup and two commercially available methods, Wesson and Saladin cards, was performed in thirty-two university students. The means slope, x-intercept and y-intercept were 0.13, -0.22 and -5.63 for Saladin; 0.01, -2.29 and -1.88 for Wesson; and 0.61, -1.33 and -2.46 for VDUET. The mean measurement test time was 582.3 s, 501.3 s and 444.8 s for Saladin, Wesson and VDUET. The FC measured by these three methods was different but not statically significant (ANOVA one-way, Tukey post-hoc test) with the exception of the slope between Wesson test and VDUET (p<0.05). The average time measurement for the VDUET was the faster by about one minute, although statically significant differences (ANOVA one-way, Tukey posthoc test) were only found between Saladin and VDUET (p<0.01). The VDUET has some features that represent some improvement over the current commercial methods for DF measurement.